2011
DOI: 10.3801/iafss.fss.10-95
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Forest Fire Propagation Research

Abstract: Forest fires are one of the major threats to natural and human built environments and have shown a tendency to increase in recent years. They are the result of several combined natural and social factors making their study and management particularly difficult and requiring the intervention of several scientific fields. One of the major issues of forest fires is associated with the combustion and propagation processes. An overview of physical processes linked to fire propagation, especially under extreme condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…During a long, dry heat-wave period, an original wildfire can occur naturally and may become uncontrolled when the weather conditions, topography, and fuels, the drivers of fire behavior, are suitable for fire spread or propagation [7,8]. From the viewpoint of ecosystem succession, a burnt forestland will recover over a long-term period of succession and consequently be suitable for the development of new communities of vegetation and wildlife [9].…”
Section: Introductionmentioning
confidence: 99%
“…During a long, dry heat-wave period, an original wildfire can occur naturally and may become uncontrolled when the weather conditions, topography, and fuels, the drivers of fire behavior, are suitable for fire spread or propagation [7,8]. From the viewpoint of ecosystem succession, a burnt forestland will recover over a long-term period of succession and consequently be suitable for the development of new communities of vegetation and wildlife [9].…”
Section: Introductionmentioning
confidence: 99%
“…Computer-based wildfire spread modeling has emerged during the past two decades as a powerful tool for applications in both fire risk management and fire emergency response. However, because the underlying wildfire dynamics feature complex multi-physics occurring at multiple scales, our ability to accurately simulate the behavior of wildfires remains limited [1]. The dynamics of wildfires are determined by interactions between pyrolysis, combustion, flow dynamics as well as atmospheric dynamics.…”
mentioning
confidence: 99%
“…An alternative approach to wildfire modelling is computational fluid dynamics (CFD)-based models such as FIRETEC (Linn 1997), FOREFIRE (Filippi et al 2009;Filippi et al 2014a) or Wildland-Urban Interface Fire Dynamics Simulator (WFDS) (Mell et al 2007). However, these are restricted to research use, and small-and particular-scale applications owing to the high computational costs and initialising data required (Viegas 2011). A simplified version of a CFD model that couples weather modelling with Rothermel's fire-spread model (Rothermel 1972) named WRF-SFIRE (Mandel et al 2014(Mandel et al , 2011 was recently reported to have been applied operationally, as a 6-h forecast could be launched with a 30-min run in a multicore processor.…”
Section: Introductionmentioning
confidence: 99%